THE STRUCTURE AND FUNCTION OF HAIR - Xamrayev Rashid Ravshan son; Qarshiyeva Shodiyo Doniyorovna (Bright Mind Publishing, 2025)
Hair is a complex and multifunctional component of the human body that serves both biological and social purposes. This article provides an in-depth exploration of the structure and functions of hair, emphasizing its composition primarily of keratin and its layered architecture, including the cuticle, cortex, and medulla. Each layer contributes uniquely to hair’s physical properties such as strength, elasticity, color, and protection. Hair growth originates from follicles located within the skin, which supply essential nutrients and support continuous development through a dynamic growth cycle. Beyond its physiological roles in protecting the scalp and other sensitive areas from environmental damage, regulating body temperature, and providing sensory feedback through nerve connections, hair also plays a vital role in human identity and cultural expression. Hairstyles and hair care practices are deeply embedded in social customs and personal identity, reflecting cultural heritage, social status, and individual creativity. By understanding the detailed anatomy and diverse functions of hair, this article highlights its significance in maintaining health, comfort, and social communication in everyday life.
Keywords: hair structure, keratin, hair follicle, cuticle, cortex, medulla, hair functions, protection, temperature regulation, sensory role, hair growth, cultural significance, personal identity.